ANALYSIS OF FACTOR AFFECTING THE INTEREST OF USING ELECTRONIC MONEY WITH TAM METHOD - Martua Hami Siregar (Kresnamedia Publisher, 2020)
The development of electronic money is currently growing very rapidly. This is marked by the rise of merchants who provide promos and ease of use of electronic money. To find out the perception of public interest in the use of electronic money, further research is needed using the Technology Acceptance Model (TAM) Method. TAM is a technology acceptance model that can be used to determine a person's perceptions of attitudes and behavior when using certain technologies. The results showed that the use of electronic money can be accepted by the public as a legal means of payment. There is a positive and significant effect of Perceived Usefulness on Attitude Towards Using, There is a positive and significant influence of Perceived Usefulness on Intention to Use, There is a positive and significant influence on Attitude Towards Using on Intention to Use and There is a positive and significant influence on Intention to Use on Actual Usage.